Molecular genetic studies in pregnancies affected by preeclampsia and intrauterine growth restriction - Abd-Rabou, Ayat Abdel-Rahman Sayed (2011)
Preeclampsia and fetal growth restriction (FGR) are common and costly obstetric complications. Both conditions are associated with immediate and remote mortality and morbidity for the mother and the offspring. Impaired placentation and aberrant maternal systemic responses are implicated as pathophysiological mechanisms in preeclampsia and FGR. Both preeclampsia and FGR are known to have a clear genetic basis. This study has investigated the roles of several candidate genes including those previously associated with diabetes (TCF7L2, FTO, PPAR-g, CDKN2B-AS1 and KCNJ11), and epidermal growth factor (EGF). Functional consequences of variants within the EGF gene were also investigated.